1993
DOI: 10.2307/3431684
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Subpopulations That Are Sensitive to Ozone Exposure: Use of End Points Currently Available and Potential Use of Laboratory-Based End Points under Development

Abstract: A number of epidemiological studies have attempted to assess the effect of recurrent ozone exposure in humans. For the most part, they have failed to document convincingly an association between chronic ozone exposure and differences in lung function performance or respiratory symptoms. This is not surprising given the small respiratory effects observed in animals chronically exposed to ozone and assuming that people with abnormal respiratory function resulting from other occupational or environmental exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The significant interindividual variation in biomarkers apparently reflects the modulating effect of genetic and acquired susceptibility factors (12). Identification of subpopulations at higher risk of detrimental effects from air pollutant exposure is needed (13).…”
mentioning
confidence: 99%
“…The significant interindividual variation in biomarkers apparently reflects the modulating effect of genetic and acquired susceptibility factors (12). Identification of subpopulations at higher risk of detrimental effects from air pollutant exposure is needed (13).…”
mentioning
confidence: 99%
“…In exposure chamber studies, ozone has been demonstrated to elicit a broad spectrum of pathophysiological responses in animals and human subjects. Responses include transient decrements in pulmonary function, 8 .9 pronounced airway inflammation, 10 -12 increased airway reactivity to bronchoconstrictor agents, 13 • 14 alterations in airway epithelial permeability,I 5 and cellular damage with epithelial remodelling in the respiratory tract. 16 • 17 Spirometric decrements 18 and airway inflammation 19 have also been observed in 'naturally' exposed individuals, namely children and adults engaged in out-door activities.…”
Section: Effects Of Ozone On Healthmentioning
confidence: 99%
“…Subsequently, a considerable body of work has been undertaken to define the effects of ozone upon the human population, 4 groups perceived as being at risk within it, 5 and in a wide range of animal models. 6…”
mentioning
confidence: 99%
“…Several epidemiologic studies have investigated the effect of recurrent ozone exposure on humans. In general, a convincing association between chronic exposure and differences in lung function performance or respiratory symptoms has not been demonstrated (50).…”
Section: Groups At Increased Riskmentioning
confidence: 99%